Controllability minimum principle based construction of the null controllable region for nonlinear systems - Mahmood, Maaz; Homer, Tyler; Mhaskar, Prashant (International journal of robust and nonlinear control, 2021)
The present manuscript addresses the problem of designing a procedure for constructing the null controllable Region (the set of states from where stabilization is achievable subject to constraints). To this end, a controllability minimum principle based computationally tractable approach for constructing the null controllable region is presented. Simulation results are used to illustrate the computation of the NCR for several examples.